Toxicity And Antioxidant Activities of Endophytic Bacteria from Butterfly Pea (Clitoria ternatea Linn.) - Zahrina, Yuni; Fitri, Lenni; Ismail, Yulia Sari; Dita, Sasmiati Farach (Biosaintifika: Journal of Biology & Biology Education, 2024)
Endophytic bacteria are bacteria that live in healthy plant tissues without causing damage. Several studies have reported that endophytic bacteria can produce active compounds similar to those secreted by their host and which potentially have medicinal value. Butterfly pea (Clitoria ternatea L.) was noted to be able to produce antioxidants and have toxicity potential from its compounds. Therefore, endophytic bacteria from butterfly pea have great potential to have antioxidant activity along with evaluating the toxicity level of the selected bacteria. This study aimed to determine the number of isolates, to characterize, and test the toxicity and antioxidant activities of endophytic bacteria from butterfly pea. Toxicity level was tested using the Brine Shrimp Lethality Test (BSLT) method while levels of antioxidants were tested using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. A total of fifteen endophytic bacteria were obtained and successfully purified. Based on the morphological observations, Gram staining, and biochemical test results, isolate EBT13 was determined to belong to the genus Bacillus. Isolate EBT13 was categorized as highly toxic, with the highest toxicity value with other bacterial isolates with an LC50 of 84 ppm and antioxidant activity with an IC50 value of 44.32 ppm. Based on the phylogenetic tree of 16S rRNA gene analysis, EBT13 belongs to the genus Bacillus, it forms a sister group with Bacillus pumilus with a bootstrap value of 100%. This study advances our knowledge of plant-microbe interactions by identifying a highly toxic, antioxidant-producing strain of bacteria of butterfly pea. The results have significance for the development of cytotoxic chemicals and natural antioxidants, which could advance biotechnological research and boost therapeutic purpose.